(3GdWH GdfaSj GdeYGUQ (B/s - (3YcGTI, CMeO,s 1935-; (3YcGTI, WGQbs ((3GdbGgQI (B:s (3ecJHI GdCfLdh GdeUQjI,s, 2020)
(3jJfGhd GdcJGH HYQV JGQjNj dJWhQGJ GdWH GdfaSj Ydi eOi GdYUhQ HOAG ef GdYUQ GdaQYhfj hGdMVGQGJ GdbOjeI Ke GdYUhQ GdeSjMjI, aEdGSdGe hMJi GdYUhQ GdMOjKI GdeYGUQI hJJHY GdeSJTajGJ GdfaSjI hGdYbdjI GdMGdjI hNGUI aj eUQ hHOAG ef GdaUd GdKGfj hMJi GdaUd GdQGHY YTQ jLeY GdeDda GdGVWQGHGJ GdfaSjI hGdYbdjI Ydi GNJdGa CSHGHgG hCfhGYgG TGQMG CYQGVgG heHjfG WQb GdYdGL(B.s
(3HHdjhLQGajI (B: (3UaMI (B977-1012.s
Keywords: (3GdWH GdfaSjs -- (3JGQjNs; (3GdUMI GdfaSjIs; (3GdYdGL GdfaSjs